Sport and eating disorders - understanding and managing the risks - Currie, A. (Asian Journal of Sports Medicine, 2010)
There is strong and consistent evidence that eating disorders are prevalent in sport and especially in weight sensitive sports such as endurance, weight category and aesthetic sports as well as jumping events. These illnesses are not only common but lead to significant physical and psychological morbidity and impaired performances. Sports organizations, and by extension the professionals whose job it is to help and support athletes, have important roles in dealing with these conditions. Preventative practices can be adopted if there is an understanding of how the sports environment contributes to the development of eating disorders. Some disorders can be difficult to detect especially in a sports environment and simple screening instruments are available. Athletes may also need help to access appropriate treatment whilst they are recovering. In many sports prevention, screening and support programs have been developed for a variety of medical conditions or sports-related injuries. Similar programs should be developed for eating disorders.